1997
DOI: 10.1107/s0021889897001040
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Small-Angle X-ray Scattering Combined with Wide-Angle X-ray Scattering

Abstract: The high X-ray intensity of synchrotron radiation (SR) beamlines makes it possible to perform time-resolved small-angle X-ray scattering (SAXS) experiments. The information that can be obtained by collecting the wideangle diffraction pattern simultaneously not only increases the information content of an experiment but also increases the reliability of the time-correlations between SAXS and WAXS (wide-angle X-ray scattering) patterns. This is a great advantage for experiments with a time resolution below the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…They also noted that the instrumentation limits in the detectors and the sample environmental chambers have hindered the experiments with shorter time resolution. For this purpose, Bras described the improved design of a dedicated station for real-time SAXS/WAXD experiments on a bending magnet beamline at the ESRF , and the development of a high-count-rate-curved PSD (1 MHz per channel) based on the microstrip gas counter (MSGC) technology for WAXD . Laggner and co-workers also reported the design of a dedicated wiggler beamline for SAXS/WAXD measurements at ELETTRA .…”
Section: Combined Techniquesmentioning
confidence: 99%
“…They also noted that the instrumentation limits in the detectors and the sample environmental chambers have hindered the experiments with shorter time resolution. For this purpose, Bras described the improved design of a dedicated station for real-time SAXS/WAXD experiments on a bending magnet beamline at the ESRF , and the development of a high-count-rate-curved PSD (1 MHz per channel) based on the microstrip gas counter (MSGC) technology for WAXD . Laggner and co-workers also reported the design of a dedicated wiggler beamline for SAXS/WAXD measurements at ELETTRA .…”
Section: Combined Techniquesmentioning
confidence: 99%
“…Data collection on single, large area CCD or future pixel detectors [50] will simplify data collection as compared to separated SAXS/WAXS detectors schemes [51].…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…Unlike Bonse-Hart SAXS cameras, the inline camera allows for fast data acquisition and makes possible time-resolved studies, as demonstrated for lower energy x-rays (Bras & Ryan, 1997). …”
Section: Development Of a High-energy Saxs Camera At Beamline 1-idmentioning
confidence: 99%